Influence of fibromucosa height and loading on the stress distribution of a total prosthesis: A finite element analysis - De Arruda Paes-Junior, Tarcisio José [UNESP]; Tribst, João Paulo Mendes [UNESP]; Dal Piva, Amanda Maria De Oliveira [UNESP]; Figueiredo, Viviane Maria Gonçalves De; Borges, Alexandre Luiz Souto [UNESP]; Inagati, Cristiane Mayumi [UNESP] (Editora Cubo, 2021)
Purpose: To evaluate the effect of fibromucosa height on the stress distribution and displacement of mandibular total prostheses during posterior unilateral load, posterior bilateral load and anterior guidance using the finite element analysis (FEA). Material and methods: 3D virtual models were made to simulate the stress generated during different mandibular movements in a total prosthesis. The contacts were simulated according to the physiology, being considered perfectly bonded between cortical and medullar bones; and between cortical bone and mucosa. Non-linear frictional contact was used for the total prosthesis base and fibromucosa, allowing the prosthesis to slide over the tissue. The cortical bone base was fixed and the 100 N load was applied as unilateral load, posterior bilateral load and anterior guidance simulation. The required results were for maximum principal stress (MPa), microstrain (mm/mm) and total displacement (mm). The numerical results were converted into colorimetric maps and arranged according to corresponding scales. Results: The stress generated in all situations was directly proportional to the fibromucosa height. The maximum principal stress results demonstrated greater magnitude for anterior guidance, posterior unilateral and posterior bilateral, respectively. Only posterior unilateral load demonstrated an increase in bone microstrain, regardless of the fibromucosa height. Prosthesis displacement was lower under posterior bilateral loading. Conclusion: Posterior bilateral loading is indicated for total prosthesis because it allows lower prosthesis displacement, lower stress concentration at the base of the prosthesis and less bone microstrain.
Keywords: Finite element analysis; Occlusion; Total prosthesis